Combination of polyherbal Phyllanthus reticulatus with Zingiber officinale and Cymbopogon citratus to optimize the antioxidant capacity - Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri; Martono, Yohanes (Pharmaciana, 2024)
Currently, the public is interested in polyherbal-based foods and beverages as a source of natural antioxidants. The aim of the study is to evaluate the antioxidant properties and the phenolic and flavonoid compounds of formulations containing Z. officinale, C. citratus, and P. reticulatus (ZCP). Each sample was extracted using the maceration process in an ethanol solvent at room temperature for three 72-hour periods. There were fourteenth formulation of Z. officinale rhizome, C. citratus leaves, and P. reticulatus fruit which used Design of Expert (DoE). The DPPH method was used to determine the power of antioxidants. The flavonoid content of the extract was measured using the colorimetric method and AlCl3 reagent, while phenolics content using Folin-Ciocalteu. The formulations ZCP 1:0:0, 0:0:1, and 1:1:1 showed the antioxidant capacity in a strong categorization, with an IC50 value less than 50 µg/ml, while ZCP 0:1:0 was in a weak categorization (IC50 > 250 µg/ml). Another ZCP formulation was in a medium category. The ZCP 1:1:1 formulation was suggested as the best one for this investigation, which contains three plant samples. This formulation is interesting for further toxicity studies and in vivo testing so that it can be applied as an antioxidant-rich supplement product.